2004
DOI: 10.1097/01.rhu.0000120900.55459.33
|View full text |Cite
|
Sign up to set email alerts
|

Relapsing Polychondritis With Encephalitis

Abstract: Central nervous system manifestations are rare in patients with relapsing polychondritis. We report a case of encephalitis associated with relapsing polychondritis. The patient presented with bilateral auricular chondritis first and then tracheal chondritis, and encephalitis developed. The symptoms and signs of encephalitis were felt mostly likely to be the result of vasculitis and improved dramatically after pulse corticosteroid therapy. We believe that early recognition of central nervous system involvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…The pathogenesis of neurologic involvement is thought to be secondary to vasculitis. This has been corroborated on autopsy studies demonstrating diffuse vasculitis of small arteries and arterioles (29). MRI of the brain also supports vasculitis as an etiology, typically showing areas of multifocal gray and white matter enhancement (29).…”
Section: Nervous System Involvementmentioning
confidence: 75%
“…The pathogenesis of neurologic involvement is thought to be secondary to vasculitis. This has been corroborated on autopsy studies demonstrating diffuse vasculitis of small arteries and arterioles (29). MRI of the brain also supports vasculitis as an etiology, typically showing areas of multifocal gray and white matter enhancement (29).…”
Section: Nervous System Involvementmentioning
confidence: 75%
“…Although CNS involvement due to vasculitis is rare, RP has been reported to be associated with aseptic meningitis, meningoencephalitis, encephalitis, and ischemic stroke (3). To our knowledge, there have been 18 cases of RP-associated meningoencephalitis and encephalitis demonstrated clinically and on neuroimaging in the English literature (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The clinical features of the previously reported cases and the present case are summarized in Table. Among these cases, the age of onset was between 29 and 73 years (mean, 55 years).…”
Section: Discussionmentioning
confidence: 89%
“…Some patients presenting with limbic encephalitis or dementia showed lesions in the temporal lobes on MRI. [14][15][16]18,20,23,24 Massry et al 10 reported that MRI in RP may be characterized by bilateral hypertensities in the basal ganglia. Addition of gadolinium enhanced smaller adjacent areas, an area in the left posterior thalamus, and a wedge-shaped area in the cortical grey matter.…”
Section: Discussionmentioning
confidence: 97%
“…Seventeen patients, including our Patients 1, 2 and 4, showed pleocytosis with a predominance of mononuclear cells, including lymphocytes and monocytes in the CSF. 6,7,9,10,[14][15][16]19,21,23,24,26 Six patients showed pleocytosis with a predominance of PMN in the CSF. 7,8,12,13,20,25 At first onset of meningoencephalitis, two patients showed pleocytosis with a predominance of mononuclear cells in the CSF, but the recurrences had a predominance of PMN 11,17 Our Patient 3 showed pleocytosis with a predominance of PMN in the CSF at first but later a predominance of mononuclear cells (Table 1).…”
Section: Discussionmentioning
confidence: 99%